A concave impeller: A new modified semi-open impeller for higher performance of centrifugal pumps - Rahmat Azis Nabawi; Egi Fadillah; Haris Shiddiq Mulyadi; Muhammad Shadiq Fahrezi; Firza Fernanda Putra (Researcher and Lecturer Society, 2025)
The performance enhancement of centrifugal pumps is continuously pursued to meet increasingly complex operational demands. Ongoing improvements in pump component design, particularly the impeller, are essential to achieving optimal configurations. The impeller is a critical component that significantly influences the overall performance of centrifugal pumps. This study aims to develop an impeller design that offers higher performance compared to the original one. The methodology utilized was Computational Fluid Dynamics (CFD). The primary focus was on modifying the semi-open impeller type. Two modified impellers were developed with concave and convex design. They were simulated and compared to the original impeller configuration. The simulation results indicate that pressure distribution at the inlet remains similar for all designs. However, pressure variations at the outlet and differences in volumetric flow rate between inlet and outlet were found. The contour visualization of pressure and flow velocity for each impeller configuration shown from the CFD simulation results is further discussed, in terms of pressure distribution and flow trajectory pressure.